2014
DOI: 10.1302/0301-620x.96b2.32680
|View full text |Cite
|
Sign up to set email alerts
|

Are cam and pincer deformities as common as dysplasia in Japanese patients with hip pain?

Abstract: In Japan, osteoarthritis (OA) of the hip secondary to acetabular dysplasia is very common, and there are few data concerning the pathogeneses and incidence of femoroacetabular impingement (FAI). We have attempted to clarify the radiological prevalence of painful FAI in a cohort of Japanese patients and to investigate the radiological findings. We identified 176 symptomatic patients (202 hips) with Tönnis grade 0 or 1 osteoarthritis, whom we prospectively studied between August 2011 and July 2012. There were 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
2
16
2
Order By: Relevance
“…In the present study, we employed an abnormal cut-off of the AAFH of >50°; namely an α-angle of >50° [3,6,8]. According to this criterion, cam deformity was detected in 51.5 % of the hips.…”
Section: Fig 3 Acetabular Anteversion Angles In the Individualmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we employed an abnormal cut-off of the AAFH of >50°; namely an α-angle of >50° [3,6,8]. According to this criterion, cam deformity was detected in 51.5 % of the hips.…”
Section: Fig 3 Acetabular Anteversion Angles In the Individualmentioning
confidence: 99%
“…However, several authors have recently reported the prevalence of FAI in Japanese populations using radiography. Mori et al [8] identified radiographic evidence of FAI in 29.7 % of patients during an investigation of OA patients with hip pain corresponding to grade 0 or 1 in the Tönnis classification. Meanwhile, Fukushima et al [9] presented radiographic evidence of radiographic FAI in 27.6 % of 87 patients who had undergone total hip arthroplasty, with no pain on the contralateral side, during the procedure in a retrospective examination.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiologic characteristics of femoroacetabular impingement (FAI) are also present in individuals without clinical symptoms either because the symptoms only develop in more advanced stages of arthrosis associated with FAI features or because FAI features in some individuals may be only an anatomic variant [38]. Radiographic features of FAI have been defined by three distinct definitions of the underlying anatomic deformity: pincer, cam, and mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior femoroacetabular impingement (FAI), a well-described cause of failure to preserve the re-orientated joint, could be another confounder for the poorer outcome after Bernese periacetabular osteotomy in Western populations. FAI is less prevalent amongst Japanese compared to Caucasians [3,8,9,11] and this could have a positive impact on the chances of preserving the re-orientated joint in this cohort. Future studies will need to address these gaps in our knowledge.…”
mentioning
confidence: 87%